Pelatihan Digital Marketing: Membuat Konten TikTok Untuk Pemasaran - Lestari, Henny Setyo; Adawiyah, Wiwik Robiatul; Ratnawati, Nirdukita; Muhammad Evirel Frasya; Maharani Dheva Dwi Safitri (Dirkantara Indonesia, 2025)
This community service activity was conducted to assist the Azalea SME Group in overcoming marketing limitations due to a low understanding of digital marketing. The objective of this activity was to enhance the participants' capacity to utilize digital media, particularly TikTok, as a marketing platform to expand market reach and increase product sales. The method used was a combination of theoretical outreach and practical training. The outreach provided basic understanding of digital marketing and the potential of TikTok as a marketing medium. The practical training covered the creation of engaging video content, the use of TikTok Ads features, and the simulation of product promotion. The evaluation of the training results was carried out through group discussions, feedback, and analysis of the video content produced by the participants. The results of the activity showed significant improvements in various aspects. Before the training, only 20% of participants understood digital marketing, but this increased to 90% after the training. The skill of creating video content increased from 10% to 85%, while the appeal of products delivered through social media rose from 15% to 75%. Additionally, the participants' interaction with consumers through social media improved from 10% to 70%. Overall, the activity demonstrated success in strengthening participants' capacity to innovate and expand marketing reach. The sustainability of the training results can be supported through follow-up training, regular mentoring, and collaboration with educational institutions and professional organizations. With this strategy, it is hoped that the Azalea SME Group can maintain the achieved success, expand business networks, and continue to grow into a competitive and high-performing business group.